Comparison of Constrained Parameterisation Strategies for Aerodynamic Optimisation of Morphing Leading Edge Airfoil - Andrea Magrini; Ernesto Benini; Rita Ponza; Chen Wang; Hamed Haddad Khodaparast; Michael I. Friswell; Volker Landersheim; Dominik Laveuve; Conchin Contell Asins (Aerospace, 2019)
In the context of ambitious targets for reducing environmental impact in the aviation sector, dictated by international institutions, morphing aircraft are expected to have potential for achieving the required efficiency increases. However, there are still open issues related to the design and implementation of deformable structures. In this paper, we compare three constrained parameterisation strategies for the aerodynamic design of a morphing leading edge, representing a potential substitute for traditional high-lift systems. In order to facilitate the structural design and promote the feasibility of solutions, we solve a multi-objective optimisation problem, including constraints on axial and bending strain introduced by morphing. A parameterisation method, inherently producing constant arc length curves, is employed in three variants, representing different morphing strategies which provide an increasing level of deformability, by allowing the lower edge of the flexible skin to slide and the gap formed with the fixed spar to be closed by a hatch. The results for the optimisation of a baseline airfoil show that the geometric constraints are effectively handled in the optimisation and the solutions are smooth, with a continuous variation along the Pareto frontier. The larger shape modification allowed by more flexible parameterisation variants enables an increase of the maximum lift coefficient up to 8.35%, and efficiency at 70% of stall incidence up to 4.26%.